2022-RA-568-ESGO Prognostic Relevance of FIGO grading is Limited to NSMP Endometrial Cancers. (20th October 2022) - Vermij, Lisa; Jobsen, Jan; Brinkhuis, Mariel; Roothaan, Suzan; Leon-Castillo, Alicia; Singh, Naveena; Mileshkin, Linda; Powell, Melanie; Ghatage, Prafull; McLachlin, Meg; Leary, Alexandra; Genestie, Catherine; et al.
Abstract : Introduction/Background: FIGO grading of endometrioid-type endometrial cancers (EEC) is standard clinical practice. Upon the incorporation of the molecular classification in the risk-assessment of EC patients, the role of grading is debated. Here, we assessed the prognostic value of grading in molecularly classified high-risk EC (HREC). Methodology: A total of 670 HREC patients from the PORTEC-3 clinical trial (n=424), and a prospective clinical cohort from Medisch Spectrum Twente in the Netherlands (n=246), were used for this study. Cases were molecularly classified following the 2020 WHO diagnostic algorithm ( POLE -mutated [ POLE mut], mismatch repair deficient [MMRd], no specific molecular profile [NSMP] and p53-abnormal [p53abn] EC). The Kaplan-Meier method, log-rank test and prespecified multivariable Cox proportional-hazard models were used for the assessment of time-to-overall-recurrence by molecular subgroup and grade. Results: In total, 433 EEC were identified, including 254 (58.7%) low-grade and 179 (41.3%) high-grade EEC. POLE mut and p53abn EEC were predominantly high-grade (n=40/45, 88.9% and n=38/46, 82.6%, respectively), while NSMP EC were mostly low-grade (n=153/180, 85.0%). Within MMRd EEC there was an equal distribution between low- and high-grade (n=88/162, 54.3% and n=74/162, 45.7%, respectively). 5-year overall recurrence was significantly lower for patients with high-grade NSMP EEC (82.7% versus 51.9%; p=0.002; figure 1A ). High-grade MMRd EEC had a slightly lower risk of recurrence than low-grade MMRd EEC, but this did not reach statistical significance ( figure 1B ). No significant differences in risk of recurrence was observed in POLE mut and p53abn EEC. Multivariable analysis confirmed independent unfavorable prognostic impact of high-grade within NSMP EEC, but not in MMRd EEC ( table 1 ). Conclusion: FIGO grading showed independent prognostic value in high-risk NSMP EEC, but not in POLE mut, MMRd or p53abn EEC. Our findings suggest that prognostic value of grading in EEC is limited to the NSMP molecular subgroup. Future studies should clarify whether this holds up in (low-)intermediate-risk EEC.